Jornal Pessoal: a agenda alternativa de Lúcio Flávio Pinto - Veloso, Maria do Socorro Furtado (Universidade de São Paulo | Escola de Comunicações e Artes, 2010)
The history reconstitution of Jornal Pessoal is the main goal of this paper. Considered as the most important and lasting experience of alternative journalism in Amazon, the newspaper has been leaded by the journalist Lúcio Flávio Pinto lonely, for 23 years. Created in 1987, in Belém (PA), it represents a model of counter-hegemonic press in Brazil in the post dictatorship period and proposes a new agenda refused by Para’s mainstream media. The Jornal Pessoal has the abse nce of advertising as one of its most important characteristics. Its editorial guideline is inspired in the I.F Stone’s Weekly, self-published for 19 years in U.S.A, by the journalist Isidore Stone. JP’s history, that survives in spite of coordinated justice trials, its interests fields, and his concerns about the foundations and practice of journalism are the axes of this investigation, that uses documental and bibliographic research, and interview.